2022
DOI: 10.1371/journal.pcbi.1009938
|View full text |Cite
|
Sign up to set email alerts
|

Novel feature selection methods for construction of accurate epigenetic clocks

Abstract: Epigenetic clocks allow us to accurately predict the age and future health of individuals based on the methylation status of specific CpG sites in the genome and are a powerful tool to measure the effectiveness of longevity interventions. There is a growing need for methods to efficiently construct epigenetic clocks. The most common approach is to create clocks using elastic net regression modelling of all measured CpG sites, without first identifying specific features or CpGs of interest. The addition of feat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…We would like to stress here, that epigenetic changes and transcriptome modifications are not necessarily correlated and thus need to be considered separately. Together they may contribute to the heritability of environmental influences, independent of the primary gene sequence alteration (Li et al 2022 ; Siwek et al 2020 ). N.B.…”
Section: Broadened Concept Of G × E: G E × E ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to stress here, that epigenetic changes and transcriptome modifications are not necessarily correlated and thus need to be considered separately. Together they may contribute to the heritability of environmental influences, independent of the primary gene sequence alteration (Li et al 2022 ; Siwek et al 2020 ). N.B.…”
Section: Broadened Concept Of G × E: G E × E ...mentioning
confidence: 99%
“…One of the most extreme results of the time effect is ageing. Biological ageing may be measured by progress on an epigenetic clock (Li et al 2022 ), i.e. a measureable alteration of the epigenetic state (G e ) over time.…”
Section: Direct Effects Of the Environment And Insult Timing On G ...mentioning
confidence: 99%
“…The potential role of epigenetics in forensic investigation lies in tissue identification of trace sample and age estimation of donor and has been described previously [ 9 , 10 ]. Prediction of age based on methylation levels in tissue is known as DNAmAge [ 11 , 12 ]. The DNAmAge may be calculated using various prediction tools and was originally proposed by Horvath in 2013 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation changes with age, and earlier work has shown that one such aggregated measure of DNA methylation forms a biomarker of chronological age (Horvath & Raj, 2018). Several ways of estimating such an 'epigenetic clock' have been developed, and enhanced epigenetic ageing has been observed in a variety of diseases, see for example Li et al (2022). Why epigenetic ageing is enhanced in such conditions, is not yet clear.…”
mentioning
confidence: 99%
“…Several ways of estimating such an ‘epigenetic clock’ have been developed, and enhanced epigenetic ageing has been observed in a variety of diseases, see for example Li et al. (2022). Why epigenetic ageing is enhanced in such conditions, is not yet clear.…”
mentioning
confidence: 99%